PENGARUH PROKRASTINASI AKADEMIK TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VII DI SMPN 1 RANAH BATAHAN - Andini; Rici Kardo; Suryadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the phenomenon of academic procrastination, which is still widely practiced by seventh grade students at SMPN 1 Ranah Batahan, such as postponing assignments, not doing homework, and submitting assignments late. The objectives of this study were to determine (1) the level of academic procrastination among students, (2) their learning outcomes, and (3) the effect of academic procrastination on learning outcomes. This study used a quantitative approach with a simple linear regression method. The population and sample in this study were 50 students (total sampling). The instrument used was a questionnaire, and the data were analyzed using percentages and simple linear regression. The results showed that (1) academic procrastination was in the high category, (2) learning outcomes (second-semester math test scores) were in the low category, and (3) there was a significant effect of academic procrastination on learning outcomes of 29.7%. This means that the higher the academic procrastination, the lower the learning outcomes. These findings provide an important basis for schools in designing strategies to reduce procrastination to improve learning outcomes. Keywords: Academic procrastination, learning outcomes, students